2016
DOI: 10.1002/pmh.1353
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder features, emotion dysregulation and non‐suicidal self‐injury: Preliminary findings in a sample of community‐dwelling Italian adolescents

Abstract: In order to assess the relationships among borderline personality disorder features, non-suicidal self-injury (NSSI) and emotion dysregulation, 122 community-dwelling Italian adolescents were administered by the Italian translations of the Borderline Personality Features Scale for Children-11, the Deliberate Self-Harm Inventory and the Difficulties in Emotion Regulation Scale (DERS). Regression models showed that both Deliberate Self-Harm Inventory (DSHI) and DERS scores significantly predicted Borderline Pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Consistent with other findings among European adolescents [19,39,40], about 26% of participants reported to have engaged in NSSI at least once in their life, and 38% had at least one episode of binge eating. As expected, our findings by using MCA technique showed that adolescents with NSSI and/or BE behaviours fell into the same category and were different from other groups of students with other types of maladaptive behaviours or none.…”
Section: Maladaptive Behaviours Clusters and Their Clinical Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with other findings among European adolescents [19,39,40], about 26% of participants reported to have engaged in NSSI at least once in their life, and 38% had at least one episode of binge eating. As expected, our findings by using MCA technique showed that adolescents with NSSI and/or BE behaviours fell into the same category and were different from other groups of students with other types of maladaptive behaviours or none.…”
Section: Maladaptive Behaviours Clusters and Their Clinical Characteristicssupporting
confidence: 89%
“…The high co-occurrence rate of these two selfdamaging behaviours suggests that similar antecedents and mechanisms may be underlying [41,42]. Several studies have found that people who engage in NSSI have a higher level of ED [40,43,44] supporting the notion that NSSI serves an emotion regulation function. In our study, adolescent students with higher depressive symptoms and ED scores were about 3 and 2.5 times more likely to belong to the NSSI-BE group.…”
Section: Maladaptive Behaviours Clusters and Their Clinical Characteristicsmentioning
confidence: 95%
“…The English version of the DSHI, originally tested among young adults in the United States, demonstrates good internal consistency and test-retest reliability, as well as adequate construct, convergent, and discriminant validity (Gratz, 2001). The DSHI has been translated into various languages, including Italian (Somma, Sharp, Borroni, & Fossati, 2017), Swedish (Lundh et al, 2007), German (Fliege et al, 2006), Dutch (Kool, van Meijel, van der Bijl, Koekkoek, & Kerkhof, 2015), and Iranian (Nobakht & Dale, 2017). Although there are differences across studies in terms of the stringency of translation and validation procedures, preliminary data suggest acceptable psychometric properties of the DSHI across translations and versions of this scale (Fliege et al, 2006;Kool et al, 2015;Latimer et al, 2013;Lundh et al, 2007;Nobakht & Dale, 2017;Somma et al, 2017).…”
Section: Psychometric Properties Of the Dshi And Isasmentioning
confidence: 99%
“…Skala ta jest popularnym narzędziem badawczym, zastosowana została m. in. w pracach "Multidimensional Assessment of Emotion Regulation Difficulties in Adolescents Using the Difficulties in Emotion Regulation Scale" [62], jak również w "Borderline personality disorder features, emotion dysregulation and non-suicidal selfinjury: Preliminary findings in a sample of communitydwelling Italian adolescents" [63]. Została opisana w artykule Marii Zetterqvist "The DSM-5 diagnosis of nonsuicidal self-injury disorder: review of the empirical literature" [39].…”
Section: Difficulties In Emotion Regulation Scale (Ders)mentioning
confidence: 99%